Prososialitas Efisien: Manifestasi Norma Sosial dalam Interaksi Mikro Transportasi Publik di Asia Tenggara - Arinal Chusnah; Estalita Kelly; Lailatuzzahro Al-Akhda Aulia (Sultan Idris Journal of Psychology and Education, 2026)
This study aims to investigate how social norms and prosocial behaviors are manifested in microinteractions in urban transit spaces in Southeast Asia. The study used a naturalistic observational qualitative approach in Jakarta, Kuala Lumpur, and Singapore, focusing on interactions in GrabCar, conventional taxis, and MRT modes. Data were obtained through observation records of 13 episodes of micro-interactions and analyzed using Reflexive Thematic Analysis (RTA). The research findings identify efficient prosociality as a category of data-driven analytics, rather than a new stand-alone theory. This concept refers to the specific form of helping behavior in urban transit spaces, namely fast, concise, function-oriented assistance, minimal verbal affective elaboration, and sensitive to time pressure and public space norms. The results showed that assistance in transit space emerged through greetings, brief conversations, navigational assistance, offers of photo assistance, and instrumental responses to situational needs. These findings show that the lack of verbal interaction does not necessarily reflect low social awareness, but can be a form of prosocial adaptation to the rhythm of urban mobility. This research emphasizes the role of civil inattention, social norms, and infrastructure design in shaping prosociality dynamics in contemporary public mobility spaces.